Virtual reality and learner autonomy in second language acquisition - Schwienhorst, Klaus (Trinity College (Dublin, Ireland). School of Education, 2001)
This thesis pursues two major areas in second language acquisition in general and computer- assisted language learning (CALL) in particular. First, it aims to provide a theoretical framework for online language learning environments on the basis of leamer autonomy and virtual reality. Second, it provides the first comprehensive empirical analysis of tandem learning, as a practical implementation of leamer autonomy, in a text-based virtual environment, the object-oriented Multiple-User Domain (MOO).
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin